PETROGENESIS AND TECTONIC IMPLICATION OF THE NEOPROTEROZOIC BONINITIC-THOLEIITIC LAVAS AND MAGNESIAN ANDESITES IN THE GORNY ALTAI TERRANE, NORTHWESTERN CENTRAL ASIAN OROGENIC BELT - Ming Chen; Min Sun; Jianping Zheng (Геодинамика и тектонофизика, 2017)
The late Neoproterozoic tholeiitic-boninitic lavas and minor magnesian andesites cropping out in the Kurai Ridge, southeast of the Gorny Altai terrane, represent magmatic products of the nascent Kuznetsk-Altai intra-oceanic island arc southwest off the Siberian continent. Samples of these rocks can provide key information about sub-arc mantle and slab-mantle interaction during the early phase of ocean-ocean subduction.